Epistaxis duration predicts bleeding in immune thrombocytopenia: a cohort study. Issue 12 (9th September 2022) - Reynolds, Lianna; Williams, Benjamin David; Grainger, John
Abstract : Objective: To test for an association between duration of epistaxis and clinically relevant bleeding in the following 12 months in children with immune thrombocytopenia (ITP). Design: Prospective cohort study. Setting: The national UK Paediatric ITP registry, a multicentre prospective clinical registry of new cases of ITP between 2006 and February 2020. Patients: All children aged between 2 months and 16 years in participating UK centres. Exposure: Epistaxis at presentation defined as none, <10 min, 10–30 min and >30 min. Main outcome measures: Incident severe bleeds, combined moderate and severe bleeds and drop in haemoglobin (Hb) by ≥20 g/L. Results: The sample included 1793 patients, of which 334 had epistaxis <10 min, 88 lasting 10–30 min and 97 >30 min. In the 12 months following presentation, 19 had a severe bleed, 140 had a moderate bleed and 54 had a drop in Hb ≥2 g/dL. Epistaxis >30 min duration was associated with increased odds of severe bleeds (OR 1.43–15.67), moderate or severe bleeding (OR 1.33–4.2) and drop in Hb (OR 1.23–6.91). Shorter duration epistaxis was not associated with increased odds of any outcome. A trend for increased odds with longer duration epistaxis was significant for all outcomes. Conclusions: The longer the duration of epistaxis at presentation with ITP, the higher the risk of a clinically significant bleeding event in the 12 months following. This should inform clinical severity ratings and treatment decisions. Abstract : This paper helps address the perennial problem of knowing which child with acute ITP is likely to suffer a significant bleed in the days, weeks and months following diagnosis. Reviewing an extensive cohort of patients the authors have identified that the risk of a 'serious/significant' bleed in the 12 months following the diagnosis of ITP is significantly increased in children who have epistaxis at presentation of greater than 30 minutes duration.